A disinhibitory microcircuit in the temporal association cortex for fear retrieval to pure tones - Rui Cheng; Wen Zhong; Yangqiu Yan; Linhui Yao; Peiran Yin; Ziyi Xu; Xiaoxia Qin; Jie Tan; Yingying Zeng; Jinhua Liu; Zhongju Xiao (Scientific Reports)
Abstract Fear retrieval is fundamental for animals to rapidly enter a self-defense state, which enhances their survival rate. Although the cellular mechanisms and neural circuits underlying fear retrieval have been relatively well studied, particularly in classic fear-related nuclei such as the amygdala, the neural circuits and intrinsic microcircuits of some non-classical fear-related nuclei remain poorly understood. A disinhibitory microcircuit in the temporal association cortex (TeA) was identified in this study, demonstrating a critical role in fear retrieval. Additionally, the response of the TeA to fear retrieval is largely driven by acetylcholine (Ach), which then relay information to the tail of striatum (TS) to mediate freezing behavior. Together, these findings demonstrate the essential role of the TeA and its microcircuit in auditory fear retrieval in response to pure tones, providing new insights into the mechanisms of fear retrieval in the cortex.